Relationship Between Learning Motivation and Self-Regulated Learning Arabic Language and Literature Students Class of 2020-2021 in Online Learning During the Covid-19 Pandemic - Della Oktariani; Lukmawati Lukmawati (Indonesian Journal of Behavioral Studies, 2022)
Abstract This study aims to determine the relationship between learning motivation with self regulated learning for Arabic Laugauge and Literatur students class of 2020-2021 in online learning during the pandemic covid-19. The population in this study were students of Arabic Language and Literatur class 2020-2021, totaling 122 students. The sample in this study were 94 students. The sampling technique used in this study is the Clutser Random Sampling method. This study uses a quantitative correlation method with Spearment analysis. All statistical calculations were carried out using the help of the SPSS version 22 Program for windows. Based on the results of the analysis, the correlation coefficient between learning motivation with self regulated learning is r = 0,523 with a significant value of 0,000 where p = < 0,05. So there is a relationship between learning motivation with self regulated learning for Arabic Laugauge and Literatur students class of 2020-2021 in online learning during the pandemic covid-19. Key words: Learning motivation, Self regulated learning, Pandemic covid-19 Abstrak Penelitian ini bertujuan untuk mengetahui hubungan antara motivasi belajar dengan self regulated learning mahasiswa Bahasa dan Sastra Arab angkatan 2020-2021 pada pembelajaran daring di masa pandemi covid-19. Populasi dalam penelitian ini adalah mahasiswa Bahasa dan Sastra Arab angkatan 2020-2021 yang berjumlah 122 mahasiswa. Sampel dalam penelitian ini adalah 94 mahasiswa. Teknik Pengambilan sampel yang digunakan dalam penelitian ini adalah metode Cluster Random Sampling (klaster), Penelitian ini menggunakan metode kuantitatif korelasi dengan analisis Spearman. Keseluruhan perhitungan statistik dilakukan dengan menggunakan bantuan program SPSS versi 22 for windows. Berdasarkan hasil analisis diperoleh besarnya koefisien korelasi antara motivasi belajar dengan self regulated learning sebesar r = 0,523 dengan nilai signifikan 0,000 dimana p = < 0,05. Maka terdapat hubungan antara motivasi belajar dengan self regulated learning mahasiswa Bahasa dan Sastra Arab angkatan 2020-2021 pada pembelajaran daring di masa pandemi Covid-19. Kata kunci: Motivasi belajar, Self regulated learning, Pandemi Covid-19